Nepal development effectiveness brief. (Metro Manila, Philippines Asian Development Bank, 2018)
Poverty in Nepal is largely a rural phenomenon, which is closely associated with limited access to finance. Only 34% of Nepals total population had access to formal financial services in 2014. Nepal was a founding member of the Asian Development Bank (ADB) in 1966. Over the years, ADB has provided assistance in several sectors, including infrastructure development, agriculture, transport, energy, water and sanitation, urban development, and education. ADB has consistently promoted gender equality and social inclusion in development, and is putting more efforts into building institutional capacity at all levels, including local governments. Climate change mitigation and environmental safeguards and good governance form part of all ADB supported projects and programs in the country.
Keywords: Administration and governance -- Nepal; Electronic books